KONSUMERISME BARAT DI INDONESIA SEBUAH TINJAUAN ULANG DARI PRESPEKTIF ISLAMIC WORLDVIEW - Syam suri; Dedy Irawan (Universitas Muhammadiyah Prof Dr Hamka, 2019)
Basically a person's consumption behavior is more influenced by his perspective on the meaning and purpose of consuming an item. So that some people are more displeased (hedonism) or just to fulfill their own needs (rationalism) caused by fanatics about the image of an item without considering the aspects of public interest (maslahah) and public harm (mafsadah). These patterns continue to be instilled in society imperialistically which eventually becomes a value, structure, social and lifestyle in community. In the Islamic concept, consumption behavior as a unity between worship and devotion is inseparable from the concept of tauhid (theocentrism). Inconsumption a Muslim must take attention to the social and economic aspects of other people. It means not only fulfilling his own needs but maqasyid sharia as a benchmark in consumption. This article tries to reconstruct the concept of Western consumption behavior which brings a lot of mafsadah and harm to society with an Islamic worldview prespective. Keywords: Consumption, Islamic Worldview, Maqashid Syari'ah